Teachers' Awareness of the Development of Perceptual Motor Functions in Pupils with Mild Intellectual Disabilities at a Primary School in the Czech Republic - Jan Viktorin; Lucie Loosová (Ignatianum University Press, 2020)
The main aim of the study was to determine teachers' awareness of the development of visual and auditory perception in pupils with mild intellectual disabilities at a mainstream school in the Czech Republic. Based on this main aim, additional goals were set: to determine to what extent teachers are aware of the importance of developing visual and auditory perception in pupils with mild intellectual disabilities, by what means teachers develop visual and auditory perception in pupils with mild intellectual disabilities, and how teachers use pupils' homework to develop visual and auditory perception. To achieve the aims of the study, the qualitative method was used with the technique of a semi-structured interview. The results show that teachers are aware of the importance of developing perceptual motor functions in pupils with mild intellectual disabilities, but the level of training in working with pupils with mild intellectual disabilities in mainstream primary schools is low. Teachers should receive more expert advice on the development of perceptual motor functions, especially from the staff of school counseling services.